A three-dimensional interpenetrated pillar-layered metal-organic framework material, a preparation method thereof and application thereof in methanol azeotrope separation

By preparing a three-dimensional interpenetrating columnar metal-organic framework material [Co2(H2MPTBDC)2(BPY-NH2)]n, and utilizing narrow channels and amino-modified organic ligands, the problem of high energy consumption in the separation of methanol azeotropes in traditional methods was solved, achieving efficient and low-cost separation.

CN120842608BActive Publication Date: 2025-11-21JINAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511373705.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-25
Publication Date
2025-11-21
Estimated Expiration
2045-09-25

AI Technical Summary

Technical Problem

Traditional methods are difficult to efficiently separate methanol from its azeotropic mixtures such as benzene, methyl acetate, dimethyl carbonate, and methyl tert-butyl ether, resulting in high energy consumption and high costs. Existing adsorption separation technologies have limited applications in the separation of azeotropic systems.

Method used

A three-dimensional interpenetrating columnar metal-organic framework material [Co2(H2MPTBDC)2(BPY-NH2)]n is used to selectively adsorb methanol through narrow channels. The methanol is then bound to amino-modified organic ligands to form hydrogen bonds, thus achieving efficient separation of methanol.

Benefits of technology

It achieves low-energy, high-efficiency separation of methanol and azeotropic components, simplifies the operation process, and reduces energy consumption and costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120842608B_ABST
    Figure CN120842608B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of chemical separation, and discloses a kind of three-dimensional interpenetrating column layer metal organic framework material and its preparation method and application in methanol azeotrope separation.The chemical formula of the metal organic framework material of the application is [Co2(H2MPTBDC)2(BPY-NH2)] n , wherein: H2MPTBDC is the first organic ligand 5-(3-methyl-5-phenyl-4H-1,2,4-triazole-4-yl) isophthalic acid, BPY-NH2 is the second organic ligand [4,4'-bipyridine]-3-amine;The metal organic framework material [Co2(H2MPTBDC)2(BPY-NH2)] n belongs to monoclinic system, and space group is P 21 / n ; the cell parameters are: a=10.59 Å, b=13.54 Å, c=30.36 Å, α=90°, β=91.52°, γ=90°.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of chemical separation technology, specifically relating to a three-dimensional interpenetrating columnar metal-organic framework material, its preparation method, and its application in the separation of methanol azeotropes. Background Technology

[0002] Azeotrope refers to a system in which a mixture of two or more liquid components forms a constant boiling point under specific conditions, and the vapor composition of the vapor phase is identical to that of the liquid phase. For example, methanol (MeOH) forms azeotropic systems with benzene (Bz), methyl acetate (MAC), dimethyl carbonate (DMC), and methyl tert-butyl ether (METB): MeOH / Bz (40 / 60, v / v), MeOH / MAC (23 / 87, v / v), MeOH / DMC (76 / 34, v / v), and MeOH / MTBE (31 / 69, v / v). Because the vapor and liquid phases have identical compositions, traditional distillation or fractionation techniques cannot directly separate azeotropic mixtures. This poses a significant challenge to purification processes in chemical production, forcing industrial manufacturers to rely on energy-intensive alternative processes such as extractive distillation, heterogeneous azeotropic distillation, and pressure swing distillation. However, these methods have significant drawbacks: extractive distillation requires the introduction of additional solvents, increasing the cost of subsequent separation steps and wastewater treatment; heterogeneous azeotropic distillation is only applicable to systems capable of liquid-liquid phase separation, limiting its applicability; and while pressure swing distillation utilizes the effect of pressure on the azeotropic composition for separation, it relies on multi-stage compression and distillation columns, resulting in extremely high energy consumption. In contrast, adsorption separation technology, due to its mild operating conditions, low energy consumption, and simple equipment, has become a highly promising alternative. This technology utilizes the selective adsorption capacity of adsorbents on different components in a mixture to achieve separation, without the need to introduce a third component or significantly change the system pressure, thereby significantly reducing energy consumption and operating costs.

[0003] Metal-organic frameworks (MOFs) are crystalline porous materials formed by the self-assembly of metal nodes and organic ligands. They possess significant advantages such as high specific surface area, precisely tunable pore size, and functionalizable pore surfaces. These properties enable MOFs to selectively capture specific molecules in mixed components based on the principle of physical adsorption, through size sieving effects, kinetic diffusion differences, or specific host-guest interactions. In the field of chemical separation, MOF materials have been successfully applied to a variety of important separation processes, including the efficient separation of light hydrocarbon gases such as ethane / ethylene and propane / propylene, and the fine separation of liquid mixtures such as hexane isomers and xylene isomers. Their separation performance is significantly superior to that of traditional adsorbent materials such as zeolites and activated carbon. However, it is worth noting that although MOFs have achieved remarkable results in hydrocarbon separation, research on their application in azeotropic systems remains relatively limited.

[0004] In industrial production, methanol often forms azeotropic mixtures with fixed compositions with compounds such as benzene (B2), methyl acetate (MAC), dimethyl carbonate (DMC), and methyl tert-butyl ether (MTBE), which affects the applications of methanol and its azeotropic components. For example, when DMC is used as a solvent in lithium-ion battery electrolytes, its azeotropic properties with methanol significantly increase the cost of obtaining high-purity DMC. Utilizing metal-organic frameworks (MOFs) to selectively adsorb methanol components from azeotropic mixtures to obtain high-purity single components and developing new MOFs for separating methanol azeotropes is of great significance for industrial production. Summary of the Invention

[0005] The purpose of this invention is to address the above-mentioned problems by providing a three-dimensional interpenetrating columnar metal-organic framework material, its preparation method, and its application in the separation of methanol azeotropes.

[0006] To achieve its objective, the present invention employs the following technical solution:

[0007] A first aspect of the present invention provides a three-dimensional interpenetrating pillar-layer metal-organic framework material, wherein the chemical formula of the metal-organic framework material is [Co2(H2MPTBDC)2(BPY-NH2)]. n Wherein: H2MPTBDC is the first organic ligand 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid, BPY-NH2 is the second organic ligand [4,4'-bipyridine]-3-amine; the metal-organic framework material is [Co2(H2MPTBDC)2(BPY-NH2)]. n It belongs to the monoclinic crystal system, space group 1. P twenty one / n The unit cell parameters are: a=10.59 Å, b=13.54 Å, c=30.36 Å, α=90°, β=91.52°, γ=90°.

[0008] The metal-organic framework material [Co2(H2MPTBDC)2(BPY-NH2)] n It has an S-shaped channel structure, which includes a bag-shaped cavity and a narrow window. The dimensions of the bag-shaped cavity are 5.44 × 9.66 × 10.46 Å. 3 The narrow window measures 3.06 Å × 4.29 Å.

[0009] The second aspect of the present invention provides a method for preparing the above-mentioned three-dimensional interpenetrating columnar metal-organic framework material, comprising the following steps: adding the first organic ligand 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid, the second organic ligand [4,4'-bipyridine]-3-amine and cobalt salt to a mixed solvent of N,N-dimethylformamide and deionized water, dissolving them completely, and then reacting them at 100~125°C to obtain purple crystals. The crystals are then washed and dried to obtain the metal-organic framework material.

[0010] In the above preparation method, preferably, the first and second organic ligands and the cobalt salt are reacted at 100~125℃ (preferably 120~125℃) for 22~72 h; after the reaction is completed, the mixture is cooled to 20~70℃ (preferably 40~70℃), filtered to obtain purple crystals, washed with N,N-dimethylformamide, and then activated by organic solvent exchange, dried to remove the solvent, thereby obtaining the metal-organic framework material.

[0011] In the above-described preparation method, preferably, the molar ratio of the cobalt salt, 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid, and [4,4'-bipyridine]-3-amine is 2:(1~2):(1~2) (preferably 2:1.5~2:1~1.5 or 2:2:1 or 1:1:1).

[0012] The volume ratio of N,N-dimethylformamide to deionized water in the mixed solvent is (0.8~1.2):(14~16);

[0013] The mass-to-volume ratio of cobalt salt to mixed solvent is (72~73) mg : (14.5~18.0) mL (preferably 72.75 mg : (14.8~17.2) mL).

[0014] In the above-mentioned preparation method, preferably, the purple crystals are washed with N,N-dimethylformamide, then exchanged with organic solvent multiple times, and then activated and dried for 12-24 hours at a temperature of 80-160℃ and a pressure of 5-6 μmHg to remove the solvent and obtain the metal-organic framework material.

[0015] In the above-described preparation method, preferably, the cobalt salt is cobalt nitrate or cobalt chloride;

[0016] The organic solvent is selected from at least one or more of acetonitrile, methanol, dichloromethane, acetone and ethanol.

[0017] A third aspect of the present invention provides the application of the three-dimensional interpenetrating columnar metal-organic framework material described in any of the preceding claims in methanol adsorption and separation.

[0018] Preferably, the metal-organic framework material is used to separate methanol azeotropic mixtures.

[0019] Preferably, the methanol azeotropic mixture contains methanol, and also contains one or more of benzene, methyl acetate, dimethyl carbonate and methyl tert-butyl ether.

[0020] The present invention has the following beneficial effects:

[0021] (1) The JNU-10-NH2 prepared in this invention is a three-dimensional interpenetrating columnar metal-organic framework formed by the reaction of the organic ligands 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid (H2MPTBDC), [4,4'-bipyridine]-3-amine (BPY-NH2), and cobalt nitrate hexahydrate. The triazole nitrogen atom and carboxylic acid oxygen atom on one H2MPTBDC ligand are coordinated with three cobalt ions, which are then connected to form a two-dimensional layered structure. The nitrogen atoms on the two pyridine rings of the pillar ligand BPY-NH2 are coordinated with the cobalt ions on the two-dimensional layers to connect adjacent two-dimensional layers to obtain a single three-dimensional network. Since there is a large void space in the single three-dimensional network, two such three-dimensional frameworks will interpenetrate each other, i.e., double interpenetration, forming a three-dimensional double interpenetrating columnar metal-organic framework.

[0022] JNU-10-NH2 of this invention is a type of ultramicroporous metal-organic framework material with S-shaped channels, wherein the channels can be subdivided into two parts: bag-shaped cavities and narrow windows, wherein the size of the bag-shaped cavities is approximately 5.44 × 9.66 × 10.46 Å. 3 The narrow window has a size of approximately 3.06 Å × 4.29 Å, which is between the values ​​of methanol (3.67 × 3.80 × 4.54 Å). 3 And ethanol 3.98×4.31×6.27 Å 3 The size of the pores allows methanol to pass through a narrow window into the pouch-like cavity, while restricting molecules larger than or comparable in size to ethanol from entering the channel. The amino group modified with the BPY-NH2 ligand, located within the pouch-like cavity, plays a crucial role in the adsorption of methanol molecules. The amino group, as a functional group, induces methanol molecules to approach each other, and then BPY-NH2 and H2MPTBDC work synergistically to form multiple CH···O, two CH···N, and one NH···O hydrogen bonds with methanol.

[0023] (2) When the two components of an azeotrope reach their azeotropic point, the proportion of the gaseous portion produced by boiling is exactly the same as that of the liquid portion, making them impossible to separate by simple distillation or fractionation. Currently, industrial separation techniques for azeotropic mixtures, such as extractive distillation, azeotropic distillation, and pressure swing distillation, all have certain limitations. Extractive distillation and homogeneous azeotropic distillation require the introduction of additional miscible solvents, increasing the cost of subsequent separation steps and wastewater treatment. Heterogeneous azeotropic distillation is only applicable to systems where liquid-liquid phase separation occurs, limiting its application range. Pressure swing distillation utilizes pressure-dependent changes in azeotropic composition, avoiding the addition of a third component, but its multi-stage compression and distillation processes result in high energy consumption. Emerging membrane separation technologies are relatively energy-efficient separation methods, but they are also limited by various factors, such as complex preparation methods, difficulty in achieving uniform pore size distribution, and efficiency losses due to polymer plasticization. The material of this invention selectively adsorbs methanol through a narrow pore window with a size between that of methanol and ethanol, and hardly adsorbs azeotropic components such as Bz, MAC, DMC and MTBE that are azeotropic with methanol, thereby achieving effective separation of methanol from azeotropic components.

[0024] (3) Synthesis of metal-organic framework material [Co2(H2MPTBDC)2(BPY-NH2)] by solvothermal method n The synthesis method is simple and the materials are relatively easy to obtain.

[0025] (4) The azeotropic components are separated by selective adsorption of metal-organic framework materials. Compared with traditional azeotropic separation methods such as extractive distillation, heterogeneous azeotropic distillation and pressure swing distillation, the energy consumption is lower and the operation is simpler. Attached Figure Description

[0026] Figure 1 This is a topological diagram of the metal-organic framework material JNU-10-NH2 prepared in Example 1.

[0027] Figure 2 This is a comparison of the adsorption isotherms of the metal-organic framework material JNU-10-NH2 prepared in Example 1 for MeOH and EtOH at 298 K.

[0028] Figure 3 This is a comparison of the vapor adsorption isotherms of the metal-organic framework material JNU-10-NH2 prepared in Example 1 for MeOH, Bz, MAC, DMC and MTBE at 298 K.

[0029] Figure 4 This is a schematic diagram of the thermal stability of the metal-organic framework material JNU-10-NH2 prepared in Example 1.

[0030] Figure 5Powder diffraction patterns of the metal-organic framework material JNU-10-NH2 prepared in Example 1 (simulated, before and after activation, and powder X-ray diffraction patterns after soaking in different pH values).

[0031] Figure 6 The adsorption heat of methanol of the metal-organic framework material JNU-10-NH2 prepared in Example 1 was measured by differential scanning calorimetry.

[0032] Figure 7 This is a schematic diagram of the interaction sites of the metal-organic framework material JNU-10-NH2 prepared in Example 1 after being loaded with methanol.

[0033] Figure 8 The column separation breakthrough curves of the metal-organic framework material JNU-10-NH2 prepared in Example 1 for a mixed liquid of MeOH / MAC (a), MeOH / DMC (b), MeOH / Bz (c) and MeOH / MTBE (d) (298 K, v:v=50 / 50).

[0034] Figure 9 These are powder X-ray diffraction patterns of the metal-organic framework materials prepared in Examples 1-4.

[0035] Figure 10 This is a comparison of the X-ray powder diffraction patterns of the metal-organic framework materials prepared in Comparative Example 1 and Example 1.

[0036] Figure 11 The comparison shows the vapor adsorption isotherms of the metal-organic framework material JNU-10 prepared in Comparative Example 1 for MeOH, Bz, MAC, DMC and MTBE at 298 K. Detailed Implementation

[0037] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

[0038] The main raw materials and their sources in the various embodiments of this invention are as follows:

[0039] Cobalt nitrate hexahydrate, CAS No.: 10026-22-9, Chemical formula: Co(NO3)2·6H2O;

[0040] N,N-Dimethylformamide (DMF): CAS No.: 68-12-2, Chemical Formula: C3H7NO;

[0041] 5-(3-Methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid (H2MPTBDC): CAS No.: 1623060-79-6, Molecular formula C 17 H 13 N3O4;

[0042] [4,4'-Bipyridine]-3-amine (BPY-NH2): CAS No.: 52311-43-0, Molecular Formula: C 10 H9N3;

[0043] 4,4'-Bipyridine (BPY): CAS No.: 553-26-4.

[0044] All of the above raw materials are commercially available conventional chemical raw materials, and all are of laboratory analytical grade.

[0045] Example 1: Preparation of the three-dimensional interpenetrating pillar metal-organic framework material of the present invention

[0046] The preparation method is performed according to the following steps: Organic ligands 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid (0.25 mmol, 80.75 mg), [4,4'-bipyridine]-3-amine (0.125 mmol, 21.53 mg), and cobalt nitrate hexahydrate (0.25 mmol, 72.75 mg) are placed in a 35 mL thick-walled pressure-resistant bottle, and then 1 mL of N,N-dimethylformamide and 14 mL of [unspecified substance] are added. Deionized water was mixed thoroughly and then ultrasonically stirred for 30 minutes to form an orange-yellow solution. At room temperature, some of the insoluble 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid was dispersed in the solution as a white suspended powder. The mixture containing the white suspended powder was placed in an oven and heated to 125°C at a rate of 5 K / min. During the heating process, the white powder gradually dissolved. After holding at 125°C for about 2 hours, the white powder completely dissolved, forming an orange-yellow solution. About 2 hours after the solid completely dissolved (i.e., after holding at 125°C for 4 hours), a small amount of purple crystals began to form. The purple crystals reached their maximum yield after holding at 125°C for another 18 hours. Extending the reaction time did not further increase the yield. The temperature was then lowered to 60°C, and the mixture was filtered while hot to prevent the precipitation of colorless crystals, resulting in purple blocky crystals. The colorless impurity crystals are recrystallized 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid ligands. Besides the previously mentioned hot filtration method to prevent precipitation, they can also be removed by soaking in DMF and ultrasonic vibration after precipitation. The obtained purple crystals were washed three times with N,N-dimethylformamide, then rapidly exchanged with methanol 10 times or soaked in methanol for 3 days, with methanol changed daily. After filtration and simple air drying, they were activated at 100°C and 6 μmHg for 24 hours to remove solvent molecules, yielding approximately 55.4 mg of the metal-organic framework material of this invention, [Co2(H2MPTBDC)2(BPY-NH2)]. n It is abbreviated as JNU-10-NH2.

[0047] Testing of JNU-11-NH2 using single-crystal X-ray diffraction confirmed that the purple crystal was the target compound. X-ray single-crystal diffraction data were collected using an XtaLAB PRO MM007-DW single-crystal diffractometer system in ω-scan mode. The X-ray generator used was an RA-Micro7HF-MR-DW (Cu / Mo), and the detector was a HyPix-6000HE Hybrid Photon Counting (HPC). The crystallographic parameters of the compound are: a = 10.59 Å, b = 13.54 Å, c = 30.36 Å, α = 90°, β = 91.52°, γ = 90°. The molecular formula is [Co2(H2MPTBDC)2(BPY-NH2)]. n H2MPTBDC is 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid, and BPY-NH2 is [4,4'-bipyridine]-3-amine.

[0048] The crystal structure topology diagram of the JNU-10-NH2 metal-organic framework material is shown below. Figure 1 As shown in the figure, JNU-10-NH2 is a three-dimensional interpenetrating metal-organic framework. Along the c-axis, JNU-10-NH2 has an S-shaped pore structure, in which the size of the bag-like cavities is approximately 5.44 × 9.66 × 10.46 Å. 3 The narrowest section has a cross-section of 3.06 Å × 4.29 Å, which is between the values ​​of methanol (3.67 × 3.80 × 4.54 Å). 3 And ethanol 3.98 × 4.31 × 6.27 Å 3 Between these sizes, molecules with molecular sizes larger than or comparable to ethanol can be excluded.

[0049] The crystallographic data of JNU-10-NH2 are shown in Table 1:

[0050] Table 1

[0051]

[0052] Single-component vapor adsorption experiments were conducted on JNU-10-NH2 using a BELSORP MAX X high-precision gas and vapor adsorption analyzer. The test temperature was 298 K, and the test pressures were the corresponding saturated vapor pressures at 298 K: methanol (16.9 kPa), ethanol (7.8 kPa), benzene (12.7 kPa), methyl acetate (22 kPa), dimethyl carbonate (5.3 kPa), and methyl tert-butyl ether (30 kPa). In subsequent plots, the unit of the horizontal axis was set to the ratio of the measured pressure P to the saturated vapor pressure P0, i.e., P / P0. The isothermal adsorption curves of JNU-10-NH2 for methanol (MeOH, kinetic dimension 3.6 Å) and ethanol (EtOH, kinetic dimension 4.3 Å) at 298 K are shown below. Figure 2 As shown, the adsorption capacities of the metal-organic framework for methanol and ethanol are 49.5 and 2.7 cm⁻¹, respectively. 2 / g, in comparison, the adsorption of ethanol is negligible, indicating that the size of the narrow window of this material is between the kinetic diameters of the two.

[0053] like Figure 3 As shown, the material preferentially adsorbs methanol. Due to the size effect, the adsorption capacities for larger azeotropic components, namely benzene (kinetic size 5.8 Å), methyl acetate (kinetic size 4.8 Å), dimethyl carbonate (kinetic size 5.2 Å), and methyl tert-butyl ether (kinetic size 6.0 Å), are 0.75, 4.97, 4.47, and 0.76 cm⁻¹, respectively. 2 / g, the adsorption capacity of these components is significantly lower than that of methanol, and the adsorption capacity of benzene and methyl tert-butyl ether is almost negligible.

[0054] like Figure 1 As shown, JNU-10-NH2 is a simple monometallic four-coordinate node, but the interpenetration of the structure enhances its stability. Thermal stability tests were performed on the material, such as... Figure 4 As shown, the material exhibits good thermal stability, with the structure only beginning to disintegrate at 400°C.

[0055] Figure 5 The image shows the powder X-ray diffraction pattern of JNU-10-NH2. The synthesized sample matches the simulated PXRD pattern, which proves the phase purity of JNU-10-NH2. Furthermore, the activated sample and the sample immersed in different acid and alkaline aqueous solutions maintain good crystallinity, indicating that JNU-10-NH2 has good stability.

[0056] The heat of methanol adsorption of JNU-10-NH2 was measured at 298 K using differential scanning calorimetry (DSC): A container containing methanol was placed in a constant temperature water bath at 25°C. 50 mL of high-purity methanol was added to a corrosion-resistant metal container connected to two corrosion-resistant metal tubes. One end of the longer tube was immersed in the methanol, and the other end was connected to nitrogen gas. One end of the shorter tube did not touch the liquid surface, and the other end was connected to an air bottle for collecting the gas. Nitrogen gas loaded with saturated methanol vapor was bubbled into the air bottle at a flow rate of 200 mL / min. The gas bottle containing the methanol / nitrogen mixture was connected to a NETZSCH STA449 F3 (Germany) simultaneous thermal analyzer to measure the heat of methanol adsorption of JNU-10-NH2 at 298 K. Figure 6 As shown, the adsorption heat of methanol measured by differential scanning calorimetry is as high as 53.8 kJ·mol⁻¹. -1 The narrow pores and the modification with amino groups give this structure a strong attraction to methanol molecules. Figure 7 The interaction between the methanol molecule and JNU-10-NH2 shown indicates that the methanol molecule is located near the carboxyl group of the organic ligand H2MPTBDC and the amino group of BPY-NH2. BPY-NH2 and H2MPTBDC work together to form multiple CH···O, two CH···N and one NH···O hydrogen bonds with methanol.

[0057] The liquid breakthrough curves of JNU-10-NH2 for MeOH / MAC, MeOH / DMC, MeOH / Bz, and MeOH / MTBE (v:v=50 / 50) under ambient conditions at room temperature are as follows: Figure 8 As shown, to standardize experimental conditions, all four azeotropic components were controlled by applying pressure with a peristaltic pump to regulate the liquid flow in the packed column, and the mixing volume ratios of the four experiments were also standardized. The figure shows that at room temperature, JNU-10-NH2 can selectively adsorb methanol to obtain high-purity methyl acetate, dimethyl carbonate, benzene, and methyl tert-butyl ether.

[0058] Example 2

[0059] The organic ligands 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid (0.125 mmol, 40.37 mg), [4,4'-bipyridine]-3-amine (0.125 mmol, 21.53 mg), and cobalt nitrate hexahydrate (0.25 mmol, 72.75 mg) were placed in a 35 ml thick-walled pressure-resistant bottle. Then, 1 mL of N,N-dimethylformamide and 14 mL of deionized water were added, and the mixture was stirred ultrasonically for 30 min. After reducing the amount of 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid, which has low solubility, the organic ligands and metal salts were completely dissolved to form an orange-yellow solution without any white powder. The orange-yellow solution was placed in an oven and heated to 125°C at a rate of 5 K / min, and held at 125°C for 22 hours. It was then cooled to room temperature. No white crystals precipitated after cooling to room temperature. The solution was filtered to obtain purple blocky crystals, which were washed three times with N,N-dimethylformamide, exchanged with methanol multiple times, and then activated at 100°C and 6 μmHg for 24 hours to remove solvent molecules. This yielded approximately 27.1 mg of the metal-organic framework material JNU-10-NH2 of this invention, a yield less than 50% of that in Example 1. It is evident that reducing the amount of 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid while keeping the amounts of [4,4'-bipyridine]-3-amine and cobalt nitrate hexahydrate constant significantly reduced the yield compared to Example 1.

[0060] Example 3

[0061] The preparation method is as follows: Organic ligands 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid (0.25 mmol, 80.75 mg), [4,4'-bipyridine]-3-amine (0.25 mmol, 43.07 mg), and cobalt nitrate hexahydrate (0.25 mmol, 72.75 mg) are placed in a 35 ml thick-walled pressure-resistant bottle. Then, 1 mL of N,N-dimethylformamide and 14 mL of deionized water are added. After mixing thoroughly, the mixture is ultrasonically stirred for 30 min to form an orange-yellow solution with a white suspended powder dispersed in the solution. The reactants containing the white suspended powder are then placed in an oven at 5°C. Heating to 125°C at a rate of K / min, the white powder gradually dissolved during the heating process. After holding at 125°C for about 2 hours, the white powder completely dissolved, forming a yellow-green solution. The solution was then held at 125°C for another 18 hours, followed by cooling to 60°C. The solution was filtered while hot to prevent the precipitation of colorless crystals, yielding purple blocky crystals. The obtained purple crystals were washed three times with N,N-dimethylformamide, then rapidly exchanged with methanol 10 times or soaked in methanol for 3 days, with the methanol being replaced daily. After filtration and simple air drying, the solution was activated at 100°C and 6 μmHg for 24 hours to remove solvent molecules, yielding approximately 56.4 mg of the metal-organic framework material JNU-10-NH2 of this invention. While keeping the amount of 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid constant, increasing the amount of [4,4'-bipyridine]-3-amine resulted in a significant color change in the solution after complete dissolution, but the same product was obtained. The weight of the product was not significantly different from that in Example 1. Combined with Examples 1-3, this indicates that the organic ligand 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid is an important factor affecting the amount of crystals obtained in the end.

[0062] Example 4

[0063] Organic ligands 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid (2.5 mmol, 807.5 mg), [4,4'-bipyridine]-3-amine (1.25 mmol, 215.3 mg), and cobalt nitrate hexahydrate (2.5 mmol, 727.5 mg) were placed in a 350 mL thick-walled pressure-resistant flask. Then, 10 mL of N,N-dimethylformamide and 160 mL of deionized water were added, and the mixture was stirred ultrasonically for 30 min to form an orange-yellow solution with a white suspended powder dispersed in it. The reactants containing the white suspended powder were placed in an oven and heated to 120 °C at a rate of 5 K / min, and held at 120 °C for 24 hours. After cooling to room temperature, the mixture was filtered, washed, and dried to obtain small purple flaky or blocky crystals. This experiment was a large-scale synthesis experiment.

[0064] Figure 9 These are the powder X-ray diffraction patterns of the metal-organic framework materials prepared in Examples 1-4. The powder X-ray diffraction patterns show that the samples obtained in Examples 2-4 are all [Co2(H2MPTBDC)2(BPY-NH2)]. n That is, JNU-10-NH2.

[0065] Comparative Example 1

[0066] The organic ligand [4,4'-bipyridine]-3-amine in Example 1 was replaced with 4,4'-bipyridine without amino modification. The preparation method was as follows: 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid (0.25 mmol, 80.75 mg), 4,4'-bipyridine (0.25 mmol, 19.52 mg), and cobalt nitrate hexahydrate (0.25 mmol, 72.75 mg) were placed in a 35 ml thick-walled pressure-resistant bottle. Then, 1 mL of N,N-dimethylformamide and 14 mL of deionized water were added. After mixing thoroughly, the mixture was ultrasonically stirred for 30 min to form a pink solution with a white suspended powder dispersed in the solution. The mixed reaction mixture was then placed in an oven at 5 °C. Heated to 125°C at a rate of K / min, held at 125°C for 24 hours, then cooled to room temperature, filtered, washed three times with N,N-dimethylformamide, and then rapidly exchanged with methanol 10 times or soaked in methanol for 3 days, with methanol changed daily. After filtering and simply drying in air, it was activated at 100°C and 6 μmHg for 24 hours to remove solvent molecules, yielding approximately 63 mg of metal-organic framework material [Co2(H2MPTBDC)2(BPY)]. n It is abbreviated as JNU-10.

[0067] The powder diffraction patterns of JNU-10 and JNU-10-NH2 are shown below. Figure 10 As shown, it is demonstrated that JNU-10 and JNU-10-NH2 prepared using 4,4'-bipyridine without amino modification are isomorphic, as shown in the figure. Figure 11 As shown, the adsorption of Bz, MAC, DMC, and MTBE by JNU-10 is negligible, but the adsorption capacity for methanol is only 30.02 cm⁻². 3 / g, with Figure 3 In comparison, the methanol adsorption capacity of this material is only three-fifths that of JNU-10-NH2, indicating that amino groups can be inserted as functional groups to improve the material's methanol adsorption capacity.

Claims

1. A three-dimensional interpenetrating columnar metal-organic framework material, characterized in that: The chemical formula of the metal-organic framework material is [Co2(H2MPTBDC)2(BPY-NH2)]. n Wherein: H2MPTBDC is the first organic ligand 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid, BPY-NH2 is the second organic ligand [4,4'-bipyridine]-3-amine; the metal-organic framework material is [Co2(H2MPTBDC)2(BPY-NH2)]. n It belongs to the monoclinic crystal system, space group 1. P twenty one / n The unit cell parameters are: a = 10.59 Å, b = 13.54 Å, c = 30.36 Å, α = 90°, β = 91.52°, γ = 90°; the metal-organic framework material is [Co2(H2MPTBDC)2(BPY-NH2)]. n It has an S-shaped channel structure, which includes a bag-shaped cavity and a narrow window. The dimensions of the bag-shaped cavity are 5.44 Å × 9.66 Å × 10.46 Å, and the dimensions of the narrow window are 3.06 Å × 4.29 Å.

2. The method for preparing the three-dimensional interpenetrating columnar metal-organic framework material according to claim 1, characterized in that, The process includes the following steps: adding the first organic ligand 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid, the second organic ligand [4,4'-bipyridine]-3-amine, and cobalt salt to a mixed solvent of N,N-dimethylformamide and deionized water, dissolving them completely, and then reacting them at 100~125℃ to obtain purple crystals. The crystals are then washed and dried to obtain the metal-organic framework material.

3. The preparation method according to claim 2, characterized in that: The first and second organic ligands and the cobalt salt were reacted at 100-125°C for 22-72 h. After the reaction was completed, the mixture was cooled to 20-70°C, filtered to obtain purple crystals, washed with N,N-dimethylformamide, activated by organic solvent exchange, and dried to remove the solvent, thus obtaining the metal-organic framework material.

4. The preparation method according to claim 2, characterized in that: The molar ratio of the cobalt salt, 5-(3-methyl-5-phenyl-4H-1,2,4-triazol-4-yl)isophthalic acid and [4,4'-bipyridine]-3-amine is 2 : (1~2) : (1~2); The volume ratio of N,N-dimethylformamide to deionized water in the mixed solvent is (0.8~1.2):(14~16); The mass-volume ratio of cobalt salt to mixed solvent is (72~73) mg : (14.5~18.0) mL.

5. The preparation method according to claim 3, characterized in that: The purple crystals were washed with N,N-dimethylformamide, then exchanged with organic solvents multiple times, and activated and dried for 12-24 hours at a temperature of 80-160℃ and a pressure of 5-6 μmHg to remove the solvent, thus obtaining the metal-organic framework material.

6. The preparation method according to claim 3, characterized in that: The cobalt salt is cobalt nitrate or cobalt chloride; The organic solvent is selected from at least one or more of acetonitrile, methanol, dichloromethane, acetone and ethanol.

7. The application of the three-dimensional interpenetrating columnar metal-organic framework material according to claim 1 in methanol adsorption and separation.

8. The application according to claim 7, characterized in that: The metal-organic framework material is used to separate methanol azeotropic mixtures.

9. The application according to claim 8, characterized in that: The methanol azeotropic mixture contains methanol, and also contains one or more of benzene, methyl acetate, dimethyl carbonate and methyl tert-butyl ether.

Citation Information

Patent Citations

  • Four metal organic frames based on Co (II) and preparation method and application thereof

    CN105367608A

  • Metal organic framework material for efficiently separating mixed gas as well as preparation method and application thereof

    CN111777769A